Práticas musicais na favela do Morro das Pedras em Belo Horizonte: um estudo crítico sobre música e modo de vida - Rubens de Oliveira Aredes (2017)
Morro das Pedras is one of the largest and oldest shankytowns of Belo Horizonte. Its origins date back to the beginnings of the history of the city, where a former black people Community (quilombo) received construction workers and migrants coming from towns in the states of Minas Gerais, Rio de Janeiro and Bahia, who all came to work in the foundation of the capital of the state, by the end of the 19th century. Today, the slum is located between two large avenues that connect noble areas to downtown, which turns it into a privileged target for real estate speculation and gentrification. At the same time, it also receives public policies and projects aiming at fighting drug trafficking. This shankytown gathers diverse musical practices, which both reflect its past and construct its present. This dissertation results from a research that aimed at studying the musical practices at Morro das Pedras, considering musical practices as human activity, and Morro das Pedras as a slum within a world where slums are getting larger and larger, as well as more numerous. Fieldwork was held in six of the twelve villages that form the shankytown, and it was developed from 2009 to 2017, focusing on the following musical practices: samba, the music within social projects (Grupo Cultural Arautos do Gueto), rap and funk. The dissertation presents a general discussion about slums and musical practices within slums in the world, in Brazil and in Belo Horizonte. Then, it focus on the ethnography, approaching the sound elements, as well as the musical, extra-musical and social elements underlying these musical practices. Finally, based on Marx’s dialectics, the work seeks to interact all the elements gathered during the ethnographic work, establishing a dialogue with the overall theoretical reference, and presenting a more global perspective about the way the participants of these musical practices live within broader social life.